2015
DOI: 10.1111/fme.12118
|View full text |Cite
|
Sign up to set email alerts
|

Sampling techniques for burbot in a western non‐wadeable river

Abstract: Burbot, Lota lota (L.), populations are declining throughout much of their native distribution. Although numerous aspects of burbot ecology are well understood, less is known about effective sampling techniques for burbot in lotic systems. Occupancy models were used to estimate the probability of detection (truep^) for three gears (6.4‐ and 19‐mm bar mesh hoop nets, night electric fishing), within the context of various habitat characteristics. During the summer, night electric fishing had the highest estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The weakness of this method was that only juveniles were captured. Day time electrofishing was performed for security reasons, even though Klein et al (2015) successfully used night electrofishing for both juvenile and adult L. lota in running waters. Therefore, electrofishing warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The weakness of this method was that only juveniles were captured. Day time electrofishing was performed for security reasons, even though Klein et al (2015) successfully used night electrofishing for both juvenile and adult L. lota in running waters. Therefore, electrofishing warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our fyke nets had smaller dimensions than the fyke nets used for L. lota sampling in other studies. Klein et al (2015) found however, that fyke nets with smaller dimensions can be more efficient than larger ones in a non-wadeable river and in contrast to Bernard et al (1991), reported a higher catch in larger than in smaller fyke nets in several lakes and the Tanana River in Alaska, U.S.A. With respect to those contradictory outcomes, the size is probably not the most important attribute and the low efficiency of fyke nets cannot be explained simply by the small dimension of the nets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WGFD is also investigating the efficacy of suppression programs (Klein et al. , , ). Anglers have become interested in participating in suppression efforts and have organized multiple ice‐fishing tournaments for Burbot on Fontenelle and Flaming Gorge reservoirs, the two primary reservoirs in the system.…”
mentioning
confidence: 99%
“…We believe that this is true and not an artifact of sampling method, as we sampled the Wind River using habitat‐targeted electrofishing, which was one of the most effective methods identified for capturing Burbot in a very similar river in the region (Klein et al. ).…”
Section: Discussionmentioning
confidence: 99%